Kisah Nabi Musa dengan Nabi Khidir dan Relevansinya dalam Pendidikan Islam - Itmam Mutaqien (ISLAMIKA, 2022)
The story of Prophet Musa and the pious servant, Prophet Khidir, is one of the stories that is full of educational values. The story is explained as explained in the Qur'an Surah Al-Kahf contained in verses 60-82. In it, it is told that when Prophet Musa met with Prophet Khidr, then the values of wisdom or lessons given by Prophet Khidir through an incident which was finally explained in a straightforward manner to Prophet Musa. The story also contains matters relating to education, especially Islamic education. This study aims to describe the stories of Prophet Musa and the pious servant, Nabi Khidir and their relevance in Islamic education. The results of this research data are obtained and processed which then the results are formulated. The research used in obtaining the data uses library research. The data were then analyzed using descriptive analysis and inductive analysis. The results showed that the stories of Prophet Musa and the pious servant, Nabi Khidir, were only limited to Surah Al-Kahf verses 60-82. In it, it is explained that Moses met Prophet Khidr, the lessons that the pious servant, the Prophet Khidir, gave to Moses and the wisdom behind the events. Then the relevance to Islamic education of the stories of Prophet Musa and Prophet Khidir are in several ways as follows: a) The purpose of Islamic education, b) educators (Nabi Khidir), c) Students (Prophet Musa), d) Methods.